Evidence for Decreased Density of Calretinin-Immunopositive Neurons in the Caudate Nucleus in Patients With Schizophrenia - Adorjan, Istvan; Sun, Bin; Feher, Virginia; Tyler, Teadora; Veres, Daniel; Chance, Steven A.; Szele, Francis G. (Frontiers in Neuroanatomy, 2020)
Schizophrenia (SCH) and autism spectrum disorder (ASD) share several common aetiological and symptomatic features suggesting they may be included in a common spectrum. For example, recent results suggest that excitatory/inhibitory imbalance is relevant in the etiology of SCH and ASD. Numerous studies have investigated this imbalance in regions like the ventromedial and dorsolateral prefrontal cortex (DLPFC). However, relatively little is known about neuroanatomical changes that could reduce inhibition in subcortical structures, such as the caudate nucleus (CN), in neuropsychiatric disorders. We recently showed a significant decrease in calretinin-immunopositive (CR-ip) interneuronal density in the CN of patients with ASD without significant change in the density of neuropeptide Y-immunopositive (NPY-ip) neurons. These subtypes together constitute more than 50% of caudate interneurons and are likely necessary for maintaining excitatory/inhibitory balance. Consequently, and since SCH and ASD share characteristic features, here we tested the hypothesis, that the density of CR-ip neurons in the CN is decreased in patients with SCH. We used immunohistochemistry and qPCR for CR and NPY in six patients with schizophrenia and six control subjects. As expected, small, medium and large CR-ip interneurons were detected in the CN. We found a 38% decrease in the density of all CR-ip interneurons (P < 0.01) that was driven by the loss of the small CR-ip interneurons (P < 0.01) in patients with SCH. The densities of the large CR-ip and of the NPY-ip interneurons were not significantly altered. The lower density detected could have been due to inflammation-induced degeneration. However, the state of microglial activation assessed by quantification of ionized calcium-binding adapter molecule 1 (Iba1)- and transmembrane protein 119 (TMEM119)-immunopositive cells showed no significant difference between patients with SCH and controls. Our results warrant further studies focussing on the role of CR-ip neurons and on the striatum being a possible hub for information selection and regulation of associative cortical fields whose function have been altered in SCH.